The emerald planet : how plants changed Earth's history - Beerling, D. J. (Oxford landmark science, 2007)
'The Emerald Planet' reveals the crucial role that plants have played in driving & recording climatic change. The book provides an important perspective on the controversial & crucial subject of global warming - for we can only understand climate change by looking into the distant past, long before the rise of humankind --